2016
DOI: 10.1111/1541-4337.12218
|View full text |Cite
|
Sign up to set email alerts
|

Overall Antioxidant Properties of Malt and How They Are Influenced by the Individual Constituents of Barley and the Malting Process

Abstract: In the past several years researchers have focused on the study of the antioxidant properties of barley and barley malt as well as their influence on beer quality. Some malt constituents have been reported as potent antioxidants due to their radical-scavenging and reducing properties, with a positive effect on beer oxidative stability. However, barley and malt can suffer some serious modifications during malting and roasting, namely on the levels of phenolic compounds and the development of Maillard reaction p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 89 publications
4
67
0
1
Order By: Relevance
“…This achieved 42-70 µg/g, or 4.9-8.3 ppm ferulic acid in the wort [11]. These numbers are in general agreement with similar studies that used different sets of barley malts [9,14,[18][19][20], however wide ranges can be found within the published literature [21]. This observed variability is most commonly linked to alternative extraction methods between researchers.…”
Section: Grains and Maltsupporting
confidence: 87%
“…This achieved 42-70 µg/g, or 4.9-8.3 ppm ferulic acid in the wort [11]. These numbers are in general agreement with similar studies that used different sets of barley malts [9,14,[18][19][20], however wide ranges can be found within the published literature [21]. This observed variability is most commonly linked to alternative extraction methods between researchers.…”
Section: Grains and Maltsupporting
confidence: 87%
“…Malting is a complex process responsible for modifications in the composition of barley. These structural changes involve many enzyme degradations, including enzymatic release of phenolic compounds bound to cellular structures of barley and with glycosylation reactions during malting, leading to easier extraction of free phenolic acids due to changes in the matrix in the early kilning (Carvalho et al 2016). Leitao et al (2012) found in their study that malting allowed a better release and/or extraction of phenolic compounds, while the first brewing step caused the most significant decrease in the total polyphenols extracted.…”
Section: Resultsmentioning
confidence: 99%
“…Among cereal grains, barley is naturally high in phenolic compounds. The majority of the barley phenolic compounds have also been identified in malt, which implies that natural antioxidants present in barley make a large contribution to the antioxidant activity of malt (Carvalho et al 2016). Therefore, the screening of different barley varieties for their antioxidant potential seems important from the aspect of malt and beer production.…”
Section: Resultsmentioning
confidence: 99%
“…Both brewing raw materials are rich in antioxidants. Barley ( Hordeum vulgare L.) contains a variety of phenolic compounds: Benzoic and cinnamic acid derivatives, hordatines, lignans and flavonoids . During malting, the phenolic content of grain extracts increases due to the enzymatic release of phenolic acids from cell‐wall polysaccharides and due to the enhanced extractability of the malted grain .…”
Section: Introductionmentioning
confidence: 99%